Study of airflow in vehicle cabin - Liu, Yusho YongXiang. (2013)
As more time is now spent on travelling and often sharing the same space, the study of airflow in a vehicle cabin is crucial in creating a comfortable and clean surrounding for passengers. Parameters determine the vehicle cabin climate and are taken into consideration for the well-being of the occupants of a vehicle cabin for perceived air quality and thermal comfort. The main focal parameters for this study are temperature, heat flux and velocity.